Butterfly (Insecta: Lepidoptera) assemblage structure along an upland-highland elevational gradient in a Brazilian tepui - Isabela Freitas OLIVEIRA; Mauro COSTA; Rafael Magalhães RABELO; Fernanda P. WERNECK; Fabricio Beggiato BACCARO (Acta Amazonica)
ABSTRACT Pantepui is a biogeographic province in the Guiana Highlands, considered an archipelago of tabletop mountains (tepuis) with a unique and poorly-known biota. Here, we investigate the butterfly assemblage structure along an elevational gradient on the Brazilian side of the Uei Tepui. We sampled butterflies in 14 plots, each at least 500 m apart, ranging from 1000 to 1820 m elevation. Each plot contained four baited traps in the canopy and four in the understory, set in pairs. We also performed standardized active sampling using an entomological net in each plot and additionally sampled butterflies opportunistically between 920 and 2100 m to complement the butterfly inventory. Over 21 days, we sampled 299 individuals from 93 species of butterflies. In the sampling plots, richness and abundance decrease considerably with altitude, and most species have been recorded (74%) in the Amazonia lowlands. However, there was a marked change in species richness, abundance, and composition at 1330 m compared to lower altitudinal plots. From this altitude, the species replacement (turnover) decreased, while the occurrence of endemic species strongly increased, especially in elevations above 1500 m. Our results highlight elevational effects such as spatial limitation and filtering on butterfly diversity, reinforcing the importance of conservation in this megadiverse region.